2010
DOI: 10.1007/s11136-010-9795-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of complementary/alternative medicines (CAMs) in a cancer population in northern Italy receiving antineoplastic treatments and relationship with quality of life and psychometric features

Abstract: CAM use is less prevalent in northern Italy than in most other European countries. CAM users were found to have a lower quality of life than CAM non-users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
19
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 24 publications
5
19
1
1
Order By: Relevance
“…Similarly, a study done in Korea by Kang et al [34] and in Germany by Tautz et al [33] found out that the global QoL of breast cancer patients between CAM consumers and nonconsumers was not different. In contrast to our finding, several previous studies [13,14] found that CAM users had a lower QoL than non-CAM users.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Similarly, a study done in Korea by Kang et al [34] and in Germany by Tautz et al [33] found out that the global QoL of breast cancer patients between CAM consumers and nonconsumers was not different. In contrast to our finding, several previous studies [13,14] found that CAM users had a lower QoL than non-CAM users.…”
Section: Discussioncontrasting
confidence: 99%
“…In recent years, studies have been conducted on CAM use and QoL and most of the studies, despite variation in study methods and definition of CAM, reported no statistically significant differences in QoL between CAM consumers and nonconsumers [10][11][12]. However, some studies reported that CAM users have a lower overall QoL than non-CAM consumers [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition a history of depression/anxiety was also associated with increased use. This finding adds to the mixed literature on this topic [26,29]. Mental health problems may both precipitate and be affected by CHA use.…”
Section: Discussionsupporting
confidence: 57%
“…Factors that enable or impede use, such as having health insurance [23,24] and financial resources [12] are generally found to be associated with higher rates of CHA use. In addition, some need characteristics (i.e., type and severity of disease [25,26], use of conventional care [26, 27], perceived quality of care [28]) are not typically associated with overall use of CHA, whereas others tend to be associated with increased use of CHA (i.e., experience of symptoms [5,25,26], more co-morbidities [14]), or have mixed results (i.e., physical health [14,18,29], mental health [14,18,29], perceived control [18,30]).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies exist in the literature examining the relationship between CAM use and QOL. [16][17][18][19][20][21] It is reported that a large proportion of cancer patients use CAM to improve their QOL and to deal with the symptoms produced by their treatment. [22][23][24][25][26] Quality of life is an individual's perception of health and is a subjective term.…”
mentioning
confidence: 99%